System impact studies for near 100% renewable energy systems dominated by inverter based variable generation - Holttinen, Hannele (2022)
ABSTRACT: The demand for low carbon energy calls for close to 100% renewable power systems, with decarbonization of other energy sectors adding to the anticipated paradigm shift. Rising levels of variable inverter-based renewable energy sources (VIBRES) are prompting questions about how such systems will be planned and operated when variable renewable generation becomes the dominant technology. Here, we examine the implications of this paradigm shift with respect to planning, operation and system stability, also addressing the need for integration with other energy vectors, including heat, transport and Power-to-X. We highlight the knowledge gaps and provide recommendations for improved methods and models needed as power systems transform towards 100% VIBRES.